Exploring Environment-Intervention Fit: A Study of a Work Environment Intervention Program for the Care Sector. (25th August 2015) - Smith, Louise Hardman; Aust, Birgit; Flyvholm, Mari-Ann
Abstract : Targeting occupational health and safety interventions to different groups of employees and sectors is important. The aim of this study was to explore the environment-intervention fit of a Danish psychosocial work environment intervention program for the residential and home care sector. Focus group interviews with employees and interviews with mangers were conducted at 12 selected workplaces and a questionnaire survey was conducted with managers at all 115 workplaces. The interventions enhanced the probability of employees experiencing more "good" work days, where they could make a difference to the lives of clients. The interventions may therefore be characterized as culturally compelling and having a good fit with the immediate work environment of employees. The interventions furthermore seemed to fit well with the wider organizational environment and with recent changes in the societal and economic context of workplaces. However, some workplaces had difficulties with involving all employees and adapting the interventions to the organization of work. The findings suggest that flexibility and a variety of strategies to involve all employees are important aspects, if interventions are to fit well with the care sector. The focus on employees' conceptualization of a "good" work day may be useful for intervention research in other sectors.